An Analysis of the Impact of the 2030 Agreement on R&D Intensity in the Energy Sector - Estevao, Joao (International Journal of Energy Economics and Policy, 2022)
European Union countries signed the 2030 Climate and Energy Framework Agreement on October 24, 2014. This framework brings with it changes in the expectations of energy consumers and producers that has opened new avenues of research. Because the 2030 Agreement imposed targets to be achieved by 2030, energy companies could increase their R&D expenditures as they search for increased efficiency through a reduction of carbon dioxide emissions and stronger base in renewable sources that promotes innovation. In addition, the risks that arise from climate change can compromise the successful achievement of the targets, such as 27% renewable energy consumption, reduction in emissions of carbon dioxide by at least 40% and to improve energy efficiency. In this study, I conduct an evaluation of the behavior of R&D intensity in this sector. It analyze the behavior of companies related to the electricity sector in two different moments, before and after the 2030 Agreement, by using panel data and comparing the listed companies with headquarters in European Union countries with companies headquartered elsewhere in Europe. The results show that the 2030 Agreement had no effect on R&D intensity in companies in the electricity sector in the countries of the European Union.